Square roots of Hamiltonian diffeomorphisms - Albers, Peter; Frauenfelder, Urs (The journal of symplectic geometry, 2014)
In this paper, we prove that on any closed symplectic manifold there exists an arbitrarily C∞-small Hamiltonian diffeomorphism not admitting a square root